Multi-Class Human Activity Prediction using Deep Learning Algorithm - Jitha Janardhanan; S. Umamaheswari (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The most common technique for understanding human behavior is action recognition based on videos. Videos provide significantly more information than image-based action recognition. Reducing action ambiguity as well as several dataset-focused studies, innovative models, and learning strategies over the past ten years have elevated video action identification to a higher level. However, there are difficulties and unresolved issues, particularly in real-time CCTV analytics where data gathering and labeling are more complex, necessitating the annotation of data. Additionally, the actions could happen very quickly, making it challenging to distinguish between them. This paper presented a video based multiple human activity recognition for real-time CCTV camera videos. To propose a HAR to introduce an Enhanced TimeSformer Model with Multi-Layer Perceptron (ETMLP) Neural Networks classification algorithm applies self-attention over the patches and human regions. By interacting with uniform classification tokens in this manner and enhancing them with contextualized human activity data, visual human pose estimation areas are able to estimate human pose.